The DressMAN 3.2-System for evaluation of thermal comfort in the Passenger Cabin Ground Demonstrator. Issue 1 (1st February 2022) - Visser, Michael; Park, Sumee; Stratbücker, Sebastian; Norrefeldt, Victor; Lindner, Andreas
Abstract: This paper describes an improved measurement method and sensor development for the assessment of the indoor thermal environment. The disadvantage of the state of the art concept of the equivalent temperature to describe inhomogeneous environments is pointed out and how the DressMAN 3.2 sensor system provides improvements to this measurement principle. The measurement system has been prepared in order to accompany thermal tests in the Passenger Cabin Ground Demonstrator developed within the CleanSky2 Regional project. This shall allow the objective assessment of the passenger comfort in the mock-up without the need for extensive subject test campaigns.